Bacteriophage-Based Bacterial Wilt Biocontrol for an Environmentally Sustainable Agriculture - Álvarez, Belén; Biosca, Elena G. (Frontiers in Plant Science, 2017)
Bacterial wilt diseases caused by Ralstonia solanacearum, R. pseudosolanacearum and R. syzygii subsp. indonesiensis (former R. solanacearum species complex) are among the most important plant diseases worldwide, severely affecting a high number of crops and ornamentals. Difficulties of bacterial wilt control by non-biological methods are related to effectiveness, bacterial resistance and environmental impact. Alternatively, a great many biocontrol strategies have been carried out, with the advantage of being environmentally friendly. Advances in bacterial wilt biocontrol include an increasing interest in bacteriophage-based treatments as a promising re-emerging strategy. Bacteriophages against the bacterial wilt pathogens have been described with either lytic or lysogenic effect but, they were proved to be active against strains belonging to R. pseudosolanacearum and/or R. syzygii subsp. indonesiensis, not to the present R. solanacearum species, and only two of them demonstrated successful biocontrol potential in planta. Despite the publication of three patents on the topic, until now no bacteriophage-based product is commercially available. Therefore, there is still much to be done to incorporate valid bacteriophages in an integrated management programme to effectively fight bacterial wilt in the field.